Pembuatan Aplikasi Informasi Properti Berbasis Web dan Android - Oeinata, Rufus Dian; Andjarwirawan, Justinus; Handojo, Andreas (Jurnal Infra, 2014)
Real estate has growth significantly in Indonesia recently, there are many new estates , apartment , shop for sale. There are several media used to advertise properties for sale, for example letâ say brochures , banners , newspapers , the internet . Among a lot of advertisement media , internet is the most effective because it does not need to pay extra fee for promotion , can load the images for the real estate , the number of people who access the Internet are very large , the search can be detailed based on user demand . Many real estate agents have promote their real estate on the internet.Â Therefore, this thesis tries to make an application that can help sellers to enter data from the real estate to be sold , and help potential buyers to search for properties in accordance with his wishes . Searches can be more effective in the presence of the coordinates on Google Maps as a property and a map service provider.Â The test results showed that the difference in screen resolution on Android devices can affect the appearance of the application on diferent device . Increasing number of data entered in the spinner will make the process of loading spinner itself is getting slow .Â